Penambahan Mikroenkapsulasi Sinbiotik (Bacillus subtilis dan Mannan oligosakarida) pada Pakan terhadap Profil Hematologi Ayam Broiler: Effect of Dietary Supplementation of Synbiotic Microencapsulation (Bacillus subtilis and Mannan oligosaccharide) on Haematological Profile of Broiler - Alditya Putri Yulinarsari; Niati Ningsih; Nur Muhamad (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
This study aimed to evaluate the effect of microencapsulation synbiotics by combining Bacillus subtilis as a probiotic and Mannan oligosaccharide as a prebiotic on the haematological profile of broilers. A total of 100 broiler chickens were used in this research. The experimental design used was a Completely Randomized Design (CRD) with 4 four treatments, namely P0: Feed + 0% Synbiotic Microencapsulation; P1: Feed + 0.25% Synbiotic Microencapsulation; P2: Feed + 0.50% Synbiotic Microencapsulation; P3: Feed + 0.75% Synbiotic Microencapsulation. The treatment was repeated 5 five times and each replication consisted of 5 broilers. Research variables carried out through laboratory testing include the number of haemoglobin, erythrocytes, hematocrit, and the erythrocyte index, namely MCV (Mean Corpuscular Volume); MCH (Mean Corpuscular Hemoglobin); MCHC (Mean Corpuscular Hemoglobin Concentration). The results showed that there was no significant difference between treatments regarding the addition of synbiotics (B. Subtilis and Mannan oligosaccharide) on the haematological profile of broilers. The conclusion of the research was that the addition of synbiotic microencapsulation (Bacillus subtilis and Mannan oligosaccharide) in feed has the potential to support growth and maintain physiological conditions but is considered not capable of maintaining a stable level of broiler health. Key words: Bacillus subtilis, broiler, Mannan oligosaccharide, synbiotic